The impact of pharmacological agents on neuroinflammation in neurodegenerative diseases - Sharma Anurag; Khan Zoya; Nath Rajendra; Dixit Rakesh Kumar (Acta Marisiensis - Seria Medica)
Neuroinflammation plays a crucial role in the progression of age-related and chronic neurological diseases, including Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. This review examines the mechanisms of neuroinflammation by focusing on microglial and astrocyte activation, key signaling pathways such as NFκB and JAK/STAT, and metabolic disturbances that modulate inflammatory processes. Pharmacological treatments, including NSAIDs, minocycline, and statins, have demonstrated some efficacy; however, their therapeutic potential is often limited by suboptimal drug delivery to the target regions and variability in patient response. The review further highlights innovative pharmacologic strategies that modulate microglial function, moving beyond the outdated M1/M2 polarization models and embracing a more dynamic view of microglial plasticity, where activation depends on the local environment and disease context. Furthermore, state-of-the-art computational and experimental drug discovery techniques are leveraged to explore novel therapies. Additionally, natural compounds such as curcumin, resveratrol, and nootropics have shown potential in modulating neuroinflammation through diverse molecular pathways. Compounds were selected based on their demonstrated clinical relevance and ability to modulate neuroinflammation through well-defined molecular mechanisms. Excluded compounds like melatonin and cannabidiol were omitted due to limited clinical data on their efficacy and concerns about off-target effects.